Suicide Risk in Dialysis: Review of Current Literature. (July 2013) - Pompili, Maurizio; Venturini, Paola; Montebovi, Franco; Forte, Alberto; Palermo, Mario; Lamis, Dorian A.; Serafini, Gianluca; Amore, Mario; Girardi, Paolo
Background: Studies have shown that patients with end-stage kidney disease (ESKD) are at risk of experiencing suicidal ideation and suicide attempt. Study Design: The aim of the present review was to investigate whether there was a relationship between dialysis and suicide. A careful systematic review of the literature was conducted to determine the potential association between dialysis and suicide. Selection Criteria for Studies: Abstracts that did not explicitly mention suicide and dialysis were excluded. We identified as specific fields of interest in the analysis of dialysis or ESRD and suicidal behavior. Results: A total of 26 articles from peer-reviewed journals were considered and the most relevant articles ( N = 13) were selected for this review. Outcomes: It has been posited that suicidal ideation, occurring in dialysis, may arise from co-morbid depression and psychiatric symptoms are frequent in patients who underwent dialysis. Limitations: The present review should be considered in the light of some limitations. We did not carry out a meta-analysis because data from most of the studies did not permit it. Samples included different measurements and different outcomes, and they assessed patients at different time points. Conclusions: The available data suggest that the risk of self-harm may be higher than expected in dialysis patients especially in those who suffer by depression and anxiety. Moreover, although the majority of deaths among dialysis patients is preceded by withdrawal from treatment, suicide remains a separate phenomenon.